ROMUALD HUBE – PIONEER IN THE TEACHING OF POLISH CRIMINAL LAW - Igor Zgoliński (Probacja, 2022)
The article presents the figure and the most important scientific achievements of Romuald Hube in the field of the science of criminal law, as well as the legislative work conducted on the criminal law of Russia and the Kingdom of Poland. Romuald Hube is undoubtedly an extremely significant figure in the Polish science of criminal law, although this branch of law was only a part of his scientific interests. It should be emphasized, however, that Romuald Hube significantly developed the science of criminal law, also in its global dimension. Moreover, through his work in the state administration, he actively participated in the creation of this branch of law. He lived and worked in an extremely complicated period due to social changes and an unfavourable geopolitical situation for Poland. Due to the fact that his life and work were associated with a foreign country, Romuald Hube was a scientist often criticized in Poland and ostracized in the community. Hube’s unquestionable contribution to the body of criminal law, with relatively little exploration of it in the doctrine, implies a need to remind the reader of the scholar’s profile.